2022
DOI: 10.1158/1078-0432.ccr-21-4235
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Prognostic Value ofCTNNB1Mutation Profile in Desmoid-Type Fibromatosis

Abstract: Purpose: This prospective nationwide cohort study aimed to investigate desmoid-type fibromatosis (DF) outcomes, focusing on the prognostic value of CTNNB1 mutations. Experimental Design: ALTITUDES (NCT02867033) was a nationwide prospective cohort study of DF diagnosed between January 2016 and December 2020. At diagnosis, CTNNB1 molecular alterations were identified using next-generation sequencing or Sanger sequencing. The primary endpoint was event-free survival (EFS) (progression, relapse, or death). We enro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Most of these cancers arise as sporadic variants. Sporadic tumors are more frequently extra-abdominal [ 2 , 34 , 35 , 36 , 37 ]. Several studies show that the inherited variant can be seen in 5–16% of patients with familial adenomatosis polyposis (FAP) [ 1 , 2 , 3 ].…”
Section: Epidemiology and Histopathologymentioning
confidence: 99%
See 4 more Smart Citations
“…Most of these cancers arise as sporadic variants. Sporadic tumors are more frequently extra-abdominal [ 2 , 34 , 35 , 36 , 37 ]. Several studies show that the inherited variant can be seen in 5–16% of patients with familial adenomatosis polyposis (FAP) [ 1 , 2 , 3 ].…”
Section: Epidemiology and Histopathologymentioning
confidence: 99%
“…Furthermore, the efficacy of marginal R1 resections remains unclear. A positive surgical margin was found to be an adverse predictor of worse local control in some series but not in others [ 3 , 34 ]. Several researchers showed that progression-free survival curves were not significantly different based on the microscopic assessment of surgical resection quality (R0 versus R1), although R2 resections resulted in a significantly poorer prognosis [ 3 , 34 ].…”
Section: Clinical Presentation and Treatmentmentioning
confidence: 99%
See 3 more Smart Citations